2021
DOI: 10.1177/14695405211013955
|View full text |Cite
|
Sign up to set email alerts
|

Inconspicuous adaptations to climate change in everyday life: Sustainable household responses to drought and heat in Czech cities

Abstract: Adaptation to climate change is often understood as a top-down decision-making and policy-implementing process, as well as application of expert knowledge, to prevent or reduce its (locally specific) negative consequences. In high-income societies, adaptation at the household level then frequently refers to adopting technological fixes distributed through the market, sometimes at a considerable cost. Informed by a study in the context of Central Europe, this article aims to discuss different practices of house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Holt asserts that "entering their lives, understanding their dreams and anxieties" [115] is needed to identify real-world concerns, needs and opportunities for change. Arguably, we should consider the benefits of scaling down, in addition to or instead of scaling up ideas and actions to reflect better the diverse and dynamic framings of climate actions among citizens [116] and pay attention to the creativity of actions anchored in people's everyday lives, which are sometimes not as "conspicuous" as tangible movements but are still influential in shaping climate mitigation and adaptation on the ground [117]. Local people play a vital role in generating knowledge by linking their ideas of their living world to broader issues [114] and enabling the creation of alternative systems providing essential services supporting local well-being and mitigating negative impacts.…”
Section: Toward More Creative Use Of Data For a Deeper Engagement Wit...mentioning
confidence: 99%
“…Holt asserts that "entering their lives, understanding their dreams and anxieties" [115] is needed to identify real-world concerns, needs and opportunities for change. Arguably, we should consider the benefits of scaling down, in addition to or instead of scaling up ideas and actions to reflect better the diverse and dynamic framings of climate actions among citizens [116] and pay attention to the creativity of actions anchored in people's everyday lives, which are sometimes not as "conspicuous" as tangible movements but are still influential in shaping climate mitigation and adaptation on the ground [117]. Local people play a vital role in generating knowledge by linking their ideas of their living world to broader issues [114] and enabling the creation of alternative systems providing essential services supporting local well-being and mitigating negative impacts.…”
Section: Toward More Creative Use Of Data For a Deeper Engagement Wit...mentioning
confidence: 99%
“…Recent work in geography has demonstrated how state politics, territorial disputes and energy regimes are shaped by the geophysical and geological characteristics of the underground, terrain, ocean and air (Elden, 2013;Steinberg and Peters, 2015;Dixon, 2021;Zee, 2022). Anthropologists have further demonstrated that energy resources are not natural things with essential qualities that are just sitting "out there" or "down there" waiting to be extracted but are brought into being through arrangements between techno-political practices, discourses and representations (Ferry and Limbert, 2008;Kneas, 2018;Richardson and Weszkalnys, 2014).…”
Section: On the Possibility Of An Anti-colonial Geopolitics -Zeynep Oguzmentioning
confidence: 99%
“…In this commentary, I underline this complexity to point out that some facets of "energy system transformation" in post-socialist CEE happening on the level of everyday life and as part of households' daily reproduction may take place indirectly, unintentionally or at least "inconspicuously" (Ferenčuhová, 2022;Shove and Warde, 2002), while others are straightforward in their political motivation -like those expressed in grassroots campaigns. Moreover, some clear-cut intentions towards change may be difficult to put into practice by individual households given their economic situation, household structure and relations between their members but also the material environment, including the existing energy infrastructures upon which they already depend.…”
mentioning
confidence: 99%
See 1 more Smart Citation